Evaluation of the Tracker Tool on the Cessna 172s Throttle Using Simulation - Dimas Endrawan Putra; Daniel Dewanto Rumani; Hadi Prayitno; Muhamad Khoirul Anam; Miftahul Asri Widiastuti Ramadhani (International Journal of Educational Research Excellence (IJERE), 2024)
The throttle is a device on the Cessna 172s training aircraft which is used to increase the amount of air used during combustion. To help overcome difficult throttle adjustments, special tools are needed in the form of a tracker. The existence of representative and useful tools to make things easier and save costs is really needed, therefore research to create work aids currently needs to be increased. Tool testing is also very important in knowing the maximum working point of the tracker tool which can determine properties such as shear elastic modulus, torsional yield strength and rupture modulus. The torsion test results consist of two parameters, namely the torsional moment parameter and the shear stress parameter. The tool that has been created in this research will analyze torsional strength using simulation.